Deletion analysis of the avermectin biosynthetic genes of Streptomyces avermitilis by gene cluster displacement. - MacNeil, T (1993)
Streptomyces avermitilis produces a group of glycosylated, methylated macrocyclic lactones, the avermectins, which have potent anthelmintic activity. A homologous recombination strategy termed gene cluster displacement was used to construct Neor deletion strains with defined endpoints and to clone the corresponding complementary DNA encoding functions for avermectin biosynthesis (avr). Thirty-five unique deletions of 0.5 to > 100 kb over a continuous 150-kb region were introduced into S. avermitilis. Analysis of the avermectin phenotypes of the deletion-containing strains defined the extent and ends of the 95-kb avr gene cluster, identified a regulatory region, and mapped several avr functions. A 60-kb region in the central portion determines the synthesis of the macrolide ring. A 13-kb region at one end of the cluster is responsible for synthesis and attachment of oleandrose disaccharide. A 10-kb region at the other end has functions for positive regulation and C-5 O methylation. Physical analysis of the deletions and of in vivo-cloned fragments refined a 130-kb physical map of the avr gene cluster region.